Polymorphism of pituitary specific transcription factor-1 (PIT-1) gene at exon 6 and its association with zoometric traits of FUNAAB Alpha chickens - Akpan Ubong; Adenaike Adeyemi Sunday; De Campos John Sunday; Lijoka Olufemi Endurance; Christian Obiora Ikeobi (Acta Scientiarum. Animal Sciences, 2025)
Pituitary specific transcription factor 1 (PIT-1) gene plays a critical role in the regulation of growth and development of muscle in chicken. This study was conducted to determine polymorphism of PIT-1 gene in FUNAAB Alpha chickens and its association with body weight and body morphometric traits (body length, thigh length, keel length wing span and wing length). Genomic DNA was extracted from ninety-seven (97) FUNAAB Alpha chickens at eight (8) weeks of age. Genotyping was done using PCR-RFLP technique and growth parameters were also recorded. Results revealed alleles A and B with genotypes AA, AB and BB which were significantly (p < 0.05) associated with body weight and body morphometric traits of chickens. BB genotype had the highest frequency of 0.52 compared with AA and AB genotypes which had 0.32 and 0.16, respectively. Particularly, the PIT-1 genotypes (AA, AB and BB) were significantly (p < 0.05) associated with body morphometric traits at 6th week. Also the interaction effect of PIT-1 genotypes and sex showed a significant (p < 0.05) association with body weight at 4th and 8th week, in which the BB males showed superior performance over the females. Our study concluded that PIT-1 gene at exon 6 was polymorphic and could be explored as biomarker for improvement of growth performance in FUNAAB Alpha chicken.